Representasi Profesionalisme Jurnalis Dalam Film The Journalist (Analisis Sepuluh Elemen Jurnalisme) - Nasya Ilmalia; Candra Darmawan (Tabayyun: Journal of Journalism, 2023)
Journalism has many interesting sides to be made into a film. There are many films and dramas that raise the theme of journalism, one of which is the film The Journalist. The Journalist, which was first released in Japan on 28 June 2019, was directed by Michihito Fujii. The film, adapted from a novel of the same name, tells the story of a young journalist named Erika Yoshioka who is asked to investigate a case about a new university construction plan that has many irregularities in it. This research is entitled "Representation of Journalist Professionalism in The Journalist Film (Ten Elements of Journalism Analysis)". This type of research is qualitative research with the Miles and Huberman model data analysis technique. This research focuses on scenes that represent the professionalism of a journalist. In this case, the researcher used the ten elements of journalism from Bill Kovach and Tom Rosenstiel as a reference to analyse how a professional journalist works, how the journalist applies the ten elements in his work as a journalist. These elements are: submission to the truth, loyalty to citizens, verification discipline, maintaining independence from news sources, being a monitor of power, providing a public forum, making important things interesting and relevant, broadcasting comprehensive and proportional news, having to follow their conscience, and citizen journalism. The result of this research is that the film The Journalist represents the professionalism of a journalist in working based on the ten elements of journalism from Bill Kovach and Tom Rosenstiel. There are scenes that provide examples of the application of the ten elements of journalism. Erika Yoshioka's character in this film illustrates how a professional journalist works.